Work engagement among breast cancer survivors: are they less engaged in their work? - , Zoharah Omar, Roohangiz Karimi, Nor Azida Nayan, Nor Aina Emran, Najwa Haneem Mohamad (Universiti Kebangsaan Malaysia, 2014)
This study investigates work engagement of employed breast cancer survivors in comparison to unmatched control samples of healthy working women without cancer and any other chronic diseases from the general population. A case-control study design using unmatched controls was adopted in this study. The case comprised of 80 female breast cancer survivors who have returned to full-time employment selected using purposive sampling technique. Meanwhile, controls were 88 healthy female working women in full time paid employment, selected using quota sampling. Questionnaire covering socio-demographic characteristics and self-rated work engagement measured using Utrecht Work Engagement Scale (UWES) was distributed to the cancer survivors through face-to-face meeting during their hospital visits. For the healthy controls the questionnaires were distributed using drop-andcollect method through the human resource personnel of the participating organization.The results revealed, after controlling for age, marital status, ethnic group and tenure with organization, no significant differences in the overall work engagement was found between the breast cancer survivors [mean (SD) =,4.66 (0.92)] and the healthy controls [mean (SD) = 4.75 (0.85)]; F(1, 163) =1.70. In comparison to the work engagement domains, only the Vigor domain was found to be significantly lower for the survivors, survivors [F (1,163) =14.94; p<.001] compared to healthy controls. However, the effect size was small (2= 0.004). No significant difference was found in the mean absorption and dedication domain scores.The findings suggest, except for vigor domain, work engagement of breast cancer survivors who have returned to work do not differ from individuals without cancer.